2015
DOI: 10.1363/4114515
|View full text |Cite
|
Sign up to set email alerts
|

Contraceptive Dynamics in Rural Northern Malawi: A Prospective Longitudinal Study

Abstract: Context-Increased use of contraceptives in Malawi has not translated into a commensurate reduction in fertility, but the reason is unknown. Insight into contraceptive switching and discontinuation may shed light on this conundrum and on whether the commonly used modern contraceptive prevalence rate (mCPR) is the best indicator of family planning program performance.Methods-A one-year prospective longitudinal data set was created from patient-held family planning cards of 4,678 reproductive-age women living in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 26 publications
2
28
1
Order By: Relevance
“…For example, in a prospective longitudinal study that used patient-held records, researchers found an 85% discontinuation rate among users of injectable contraception in rural northern Malawi. 9 However, the point estimate of the prevalence of modern contraceptive use that these researchers calculated using their longitudinal data was lower than modern contraceptive use estimates reported from other cross-sectional surveys for this population. This suggests that conventional estimates of contraceptive use might be overestimates if, when responding to survey questions about past use, women consider themselves to be contraceptive users even if they were late for re-injection.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…For example, in a prospective longitudinal study that used patient-held records, researchers found an 85% discontinuation rate among users of injectable contraception in rural northern Malawi. 9 However, the point estimate of the prevalence of modern contraceptive use that these researchers calculated using their longitudinal data was lower than modern contraceptive use estimates reported from other cross-sectional surveys for this population. This suggests that conventional estimates of contraceptive use might be overestimates if, when responding to survey questions about past use, women consider themselves to be contraceptive users even if they were late for re-injection.…”
Section: Discussionmentioning
confidence: 61%
“…8 Injectables are the most widely used modern method in Malawi: nearly a third of currently married women (30%) who practised modern family planning in 2015-16 used injectables. However, according to findings from a study in rural Malawi, 9 only half of new users received their first follow-up injection within 13 weeks, and method switching is not common among women who discontinue for method-related reasons. 5 In a study from 2012, 38% of women in Malawi who did not switch to another method after discontinuing for method-related reasons became pregnant and more than half of those pregnancies were either mistimed or unwanted.…”
Section: Introductionmentioning
confidence: 99%
“…Elsewhere we show high discontinuation of short-term methods in northern Malawi [16]. Therefore, provision of short-term methods in the immediate postpartum period is unlikely to be effective, given the low risk of pregnancy for women during this time and high probability of discontinuation by the time the woman resumes sexual activity and menstruation [17].…”
Section: Discussionmentioning
confidence: 85%
“…However, recent increases in contraceptive use in Malawi have not translated into lower fertility rates [26]. Several plausible explanations for this seeming disconnect have been put forward, including that contraceptive increases may be occurring among women at lower risk of pregnancy, or potentially due to contraceptive discontinuation [32]. Furthermore, simultaneous increases in contraception and abortion can occur in the context of concurrent increases in desire for smaller family size [33].…”
Section: Discussionmentioning
confidence: 99%